Services et développement urbains au Venezuela - Anne Péné-Annette (Cahiers des Amériques Latines)
The access to urban basic utilities, particularly water supply is one of the most interesting ways to realize the urban life conditions in Venezuela and examine the participative reforms. First, we begin with LOPSAPS water and sanitation law analysis. Then, we focus to water supply management and we wonder how social justice is applied in urban areas. We take the case of Puerto La Cruz city located on eastern coast. In this town, an inventive politics is realized by a dynamical social participation in water supply.